2020
DOI: 10.5812/zjrms.77180
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Obesity and Sexual Function in Iranian Women

Abstract: Background: Obesity is a chronic disease and threatening factors of public health. Obese people have negative body image, and low self-confidence can lead to sexual dysfunction. Objectives: This study aimed to investigate the relationship between obesity and sexual function in women referred to health centers of Birjand in Iran. Methods: This cross-sectional study was conducted on 126 married women who were selected via a multi-stage sampling method from Birjand Health centers in 2014. The participants were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In this study we found that the mean age of the studied cases was 34.16 (±5.75 SD) with range (26-48), among the studied cases there were 36 (40%) urban residents and 54 (60%) rural residents, and all the studied cases were with high education. Adolfsson et al (9) reported that obese women aged 18-49 years old experienced the greatest decrease in sexual desire, compared to a normal weight group. Although there were no differences in sexual dysfunction (lack of sexual desire, arousal problems, and painful intercourse) observed among overweight, obese and normal-weight women, Bajos et al (10) showed a significant trend towards decreasing sexual desire with increasing BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we found that the mean age of the studied cases was 34.16 (±5.75 SD) with range (26-48), among the studied cases there were 36 (40%) urban residents and 54 (60%) rural residents, and all the studied cases were with high education. Adolfsson et al (9) reported that obese women aged 18-49 years old experienced the greatest decrease in sexual desire, compared to a normal weight group. Although there were no differences in sexual dysfunction (lack of sexual desire, arousal problems, and painful intercourse) observed among overweight, obese and normal-weight women, Bajos et al (10) showed a significant trend towards decreasing sexual desire with increasing BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, obese females exhibit a higher prevalence of FSD, ranging from 50% to 86%, and this is correlated with a higher body mass index (BMI), which significantly impacts their sexual quality of life [ 14 ]. Despite the importance of promoting sexual function in obese females with sexual dysfunction, which is a crucial aspect of females' healthcare [ 15 ], there is limited evidence regarding the specific impact of weight loss on improving sexual function, particularly within the Arab world.…”
Section: Introductionmentioning
confidence: 99%
“…Although sexual function promotion in obese women having sexual dysfunction represents a very important topic in women’s health care ( Karimi et al, 2020 ), there is very little evidence on the influence of weight loss only on sexual function improvement, particularly in the Arab world. Therefore, this study aimed to evaluate the effect of a weight loss program on sexual function, psychological health, and quality of life among a sample of obese Egyptian married women having sexual dysfunction.…”
Section: Introductionmentioning
confidence: 99%